2021
DOI: 10.1038/s41598-021-88000-5
|View full text |Cite
|
Sign up to set email alerts
|

Vegfa promoter gene hypermethylation at HIF1α binding site is an early contributor to CKD progression after renal ischemia

Abstract: Chronic hypoxia is a major contributor to Chronic Kidney Disease (CKD) after Acute Kidney Injury (AKI). However, the temporal relation between the acute insult and maladaptive renal response to hypoxia remains unclear. In this study, we analyzed the time-course of renal hemodynamics, oxidative stress, inflammation, and fibrosis, as well as epigenetic modifications, with focus on HIF1α/VEGF signaling, in the AKI to CKD transition. Sham-operated, right nephrectomy (UNx), and UNx plus renal ischemia (IR + UNx) gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 66 publications
1
14
0
Order By: Relevance
“…Meanwhile, KLF4 promoted the expression of VEGFA in HEMECs, triggered VEGFA secretion and subsequent blood vessel formation ( Figures 4 A–4D and S2 B–S2C). VEGFA promoter contain share considerable binding sites for Sp1/Sp3, AP-1, Egr-1, STAT-3, HIF1α, KLF8, KLF4, YY1 at the proximal region of promoters from various species ( Cheng et al., 2018 ; Sanchez-Navarro et al., 2021 ; Shima et al., 1996 ; Wang et al., 2015 ; Yang et al., 2019 ). In HEMECs, we found that KLF4 bound to ∼0.6 kb region of the VEGFA promoter which contain “CACCC” sites, suggesting that KLF4 can transcriptionally activate VEGFA ( Figure 4 J) and form a positive feedback loop with VEGFA to promote endometrial angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, KLF4 promoted the expression of VEGFA in HEMECs, triggered VEGFA secretion and subsequent blood vessel formation ( Figures 4 A–4D and S2 B–S2C). VEGFA promoter contain share considerable binding sites for Sp1/Sp3, AP-1, Egr-1, STAT-3, HIF1α, KLF8, KLF4, YY1 at the proximal region of promoters from various species ( Cheng et al., 2018 ; Sanchez-Navarro et al., 2021 ; Shima et al., 1996 ; Wang et al., 2015 ; Yang et al., 2019 ). In HEMECs, we found that KLF4 bound to ∼0.6 kb region of the VEGFA promoter which contain “CACCC” sites, suggesting that KLF4 can transcriptionally activate VEGFA ( Figure 4 J) and form a positive feedback loop with VEGFA to promote endometrial angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…The VEGFA levels were decreased after 5-aza-dC treatment in both European-H and African-L cybrids, indicating that its transcription levels are regulated by methylation in the cybrid model. Sanchez-Navarro et al reported that DNA hypermethylation of the VEGFA promoter gene leads to lower levels of HIF-1α/VEGFA signaling [ 58 ]. In the VEGFA promoter region, the HIF1 Binding Site (HBS) is demethylated and the HIF1α/HIF1β complex binds to the promoter to upregulation of VEGF expression [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Eighteen genes with persistent alterations in DNA methylation induced by IRI for 7 days, as well as persistent changes in gene expression, were identified, suggesting that persistent promoter methylation contributes to the pathophysiology of AKI-to-CKD transition ( Zhao et al, 2017 ). Others analyzed DNA methylation and gene expression in a rat model of IRI, focusing on HIF1α/VEGF signaling at 1, 2, 3, and 4 months after IRI ( Sanchez-Navarro et al, 2021 ). Rats that experience IRI exhibit a persistent reduction in global DNA methylation during the entire experiment; and the reduction of HIF1α/VEGF signaling triggered after IRI, which may trigger renal hypoxia, is accompanied by persistent hypermethylation at the HIF-1α binding site of the Vegfα promoter throughout the observational periods ( Sanchez-Navarro et al, 2021 ).…”
Section: Epigenetic Memory In Aki-to-ckd Transition: Persistent Epige...mentioning
confidence: 99%
“…Others analyzed DNA methylation and gene expression in a rat model of IRI, focusing on HIF1α/VEGF signaling at 1, 2, 3, and 4 months after IRI ( Sanchez-Navarro et al, 2021 ). Rats that experience IRI exhibit a persistent reduction in global DNA methylation during the entire experiment; and the reduction of HIF1α/VEGF signaling triggered after IRI, which may trigger renal hypoxia, is accompanied by persistent hypermethylation at the HIF-1α binding site of the Vegfα promoter throughout the observational periods ( Sanchez-Navarro et al, 2021 ). Thus, DNA methylation, similar to its role in DKD, is a strong candidate for epigenetic memory in AKI-to-CKD transition.…”
Section: Epigenetic Memory In Aki-to-ckd Transition: Persistent Epige...mentioning
confidence: 99%
See 1 more Smart Citation